Association of long-term use of dipeptidyl peptidase-4 inhibitors with the risk of diabetic retinopathy in patients with diabetes mellitus: a real-world evidence study - Li, Yu-Ching; Kuan, Yu-Hsiang; Yang, Yih; Gau, Shuo-Yan; Su, Kun-Yu; Tsai, Tung-Han; Huang, Kuang-Hua; Lee, Chien-Ying (Frontiers in Pharmacology, 2025)
BackgroundIn this study, we investigated the association of long-term use of a dipeptidyl peptidase-4 inhibitor (DPP-4i) with the risk of diabetic retinopathy (DR) in patients with diabetes mellitus (DM).MethodsThis study was a secondary analysis based on the nationwide database from 2008 to 2022 in Taiwan. Patients with new-onset DM who were treated with either a DPP-4i or sulfonylurea from 2009 to 2017 were included in this study. Patients who received a DPP-4i were included in the case group and further divided on the basis of the cumulative defined daily dose (cDDD) as follows: ≤90, 91–180, 181–300, and >300 cDDD. Propensity score matching was performed to select patients who used a sulfonylurea, and these patients were assigned to the control group. With adjustment for sex, age, income, urbanization level, comorbidities, and other anti-diabetic agents, the Cox proportional hazard model was used to estimate the risk of DR associated with DPP-4i use over the 5-year follow-up.ResultsThere were 83,503 patients with DPP-4i use and 167,006 patients with sulfonylurea use after matching. Compared with patients with sulfonylurea use, patients with DPP-4i use at ≤90 cDDD had a hazard ratio (HR) of 1.43 (95% confidence interval [CI] = 1.38–1.49) for DR development, whereas those with DPP-4i use at 91–180, 181–300 or >300 cDDD had HRs of 1.66 (95% CI: 1.59–1.74), 1.82 (95% CI: 1.74–1.90), and 2.32 (95% CI: 1.91–2.82) for DR development, respectively. Of the different DPP-4is, linagliptin at ≤90 or 181–300 was associated with the highest risk of DR. Significant differences were discovered at ≤90, 91–181, and 181–300 cDDD in the risk of DR between patients using Saxagliptin versus sitagliptin. Vildagliptin at ≤90 or 91–180 cDDD was associated with an increased risk of DR, but not at 181–300 cDDD.ConclusionIn patients with DM, DPP-4i at ≤90, 91–180, 181–300 and >300 cDDD was linked to an increased risk of DR over the 5-year follow-up. Sitagliptin at cDDD 181–300 was associated with the greatest DR risk. The potential for DPP-4i to accelerate DR progression should be considered.